Teaching Aids Practices in Facilitation of 21st Century’s Quranic Tilawah among Islamic Education Teachers - Jalil, Mohd Zabani; Ismail, Ashraf; Usman, Abur Hamdi (International Journal of Psychosocial Rehabilitation, 2020)
Teaching Aids (TA) is a tool used by teachers in the Learning and Facilitation (L&F) process. Since the advent of 21st Century Learning (PAK-21), the use of TA has been considered very important for teachers in facilitating L&F. The use of TA can help teachers to convey knowledge and information on a particular subject more clearly and systematically and can attract students. Therefore, the researchers want to explore the teaching aids implementation in the facilitation of the 21st-Century’s Quranic tilawah among Islamic Education Teachers (IET) in primary schools in the State of Malacca. This study is a field-based case study that involved four IETs study participants from four different schools in Malacca. The data collected through interviews and observations were then analysed using Nvivo 12 software. The findings of the study show that the four study participants practiced the use of teaching aids in the facilitation of Quranic tilawah. The findings also show that there are three main types of TA used in facilitating L&F in the 21st Century’s Quranic tilawah: ICT (computer and LCD), printed TA (textbook), and hearing TA (microphone and speaker). The findings also show that the most commonly used TAs are the ICT TA, which is the computer and LCD. It is hoped that this finding will serve as a guide to further the practice of TA among IETs in order to attract students’ interest in L&F Quranic tilawah, especially within the 21st Century generations.